2022
DOI: 10.1029/2021gb007285
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Soil Extracellular Enzyme Activities to Salinization: Implications for Soil Carbon Cycling in Tidal Wetlands

Abstract: Rising sea levels are expected to cause salinization in many historically low‐salinity tidal wetlands. However, the response of soil extracellular enzyme activities to salinization in tidal wetlands and their links to soil organic carbon (SOC) decomposition are largely unknown. Here, we conducted a global meta‐analysis to examine the effect of salinization on hydrolytic and oxidative carbon‐acquiring enzyme activities and their relationships with SOC storage in tidal wetlands. The results showed that salinizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 108 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…Seven kinds of extracellular enzymes involved in SOC decomposition were included in this meta‐analysis (Table S2) following previous studies (Chen et al ., 2018 a ; Margida et al ., 2020; Ren et al ., 2017; Yang et al ., 2022 b ): four cellulases [β‐1,4‐glucosidase (BG), α‐1,4‐glucosidase (AG), β‐1,4‐xylosidase (BX) and β‐D‐cellobiosidase (CBH)] and three ligninases [phenol oxidase (PO), polyphenol oxidase (PPO) and peroxidase (PER)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven kinds of extracellular enzymes involved in SOC decomposition were included in this meta‐analysis (Table S2) following previous studies (Chen et al ., 2018 a ; Margida et al ., 2020; Ren et al ., 2017; Yang et al ., 2022 b ): four cellulases [β‐1,4‐glucosidase (BG), α‐1,4‐glucosidase (AG), β‐1,4‐xylosidase (BX) and β‐D‐cellobiosidase (CBH)] and three ligninases [phenol oxidase (PO), polyphenol oxidase (PPO) and peroxidase (PER)].…”
Section: Methodsmentioning
confidence: 99%
“…Soil extracellular enzymes catalyse the degradation of soil organic matter, deconstructing plant and microbial residues by breaking down large macromolecules into simpler molecules (Margida, Lashermes & Moorhead, 2020; Sinsabaugh, 2010). Various extracellular enzymes target different pools of SOC, for example, ligninases target structurally complex polyphenolic macromolecules, and cellulases degrade ordered polysaccharides with a simpler structure (Chen et al ., 2018 a ; Margida et al ., 2020; Ren et al ., 2017; Yang et al ., 2022 b ). Biochar addition may have different impacts on ligninase and cellulase activity, partly due to changes in the chemical composition of soil organic matter and also due to shifts in microbial community composition (Gul et al ., 2015; Jing et al ., 2022; Singh & Cowie, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that enzyme activity rates are highest in surface or near-surface soils and decrease with depth (Minick et al 2022) likely due to the in ux of fresh OM that stimulates microbial activity in sediment surfaces (Naylor et al 2020). A recent global meta-analysis showed that hydrolytic Cacquiring enzyme activity is negatively correlated with salinity (Yang et al 2022). Given that processing and protection takes place in different micro-sites within the sediment matrix, grain size distribution is an important factor (Kravchenko et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plant‐derived SOM, such as lignin, increased with fraction size increase (Angst et al, 2021), and microbial residues enriched in fine‐sized minerals relatively (Han et al, 2016). During soil salinisation, SOM storage decreases (Kim et al, 2017; Yang et al, 2022), meanwhile, Ca 2+ , Mg 2+ , and other multivalent cations are gradually replaced by Na + at soil exchangeable sites, which worsen soil structure (Wong et al, 2010). Straw input could effectively improve saline soil aggregate formation and stability (Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During soil salinisation, SOM storage decreases (Kim et al, 2017;Yang et al, 2022), meanwhile, Ca 2+ , Mg 2+ , and other multivalent cations are gradually replaced by Na + at soil exchangeable sites, which worsen soil structure (Wong et al, 2010). Straw input could effectively improve saline soil aggregate formation and stability (Xie et al, 2020).…”
mentioning
confidence: 99%